Eksistensi Laporan Nilai Tambah Syariah Berbasis Rezeki - Aji Dedi Mulawarman (The Indonesian Journal of Accounting Research, 2013)
The objective of this study is to prove evidence of the existence Shari'ate Value Added Statement from the real transaction and business habitues of Indonesian Moslem society. Utilising Hyperphenomenology Methods, I show that rizq is a substance of  Shari'ate Value Added (SVA) concept. Rizq is a form of income called rizq income. This type of income can be observed empirically in everyday life of Indonesian Moslem society. I argue that rizq is actually value added gained (financially, socially, and environmentally) and has been purified (becomes halal, thoyib, and free from riba) in every step of its attainment, until its distribution. As a consequence, the quantitative and qualitative elements of the Shari'ate Value Added Statement can not presented separately.